EPIDEMIOLOGICAL CHARACTERISTICS OF OUTBREAKS OF HAND, FOOT AND MOUTH DISEASE IN KINDERGARTENS IN BELGRADE DURING THE PERIOD FROM 2015 TO 2019 - Giljaca, Sonja; Maris, Slavica; Rancic, Natasa; Mrvaljevic, Milutin; Mrvaljevic, Zorica (HEALTH CARE, 2021)
Introduction/Aim: For the first time in the world Hand, Foot and Mouth Disease was reported in 1957 in Canada, while the first outbreak of this disease was registered in Belgrade in 2014.The aim of this paper is to analyze epidemiological characteristics of outbreaks of HFMD, which occurred in kindergartens in Belgrade in the period from 2015 to 2019. Methods: A descriptive epidemiological study was applied. Data were collected from epidemiological questionnaires, Reports of Center for Disease Control and Prevention, City Institute of Public Health Belgrade, from the case history of sick children, and using the results of the virological and serological analyses that had been done in the Reference Laboratory of the Institute of Virology, Vaccines, and Sera “Torlak”. Results: In the period from 2015 to 2019, 20 HFMD outbreaks were registered, in which a total of 220 children became ill. The total number of infected children in outbreaks ranged from 9 to 102. Boys were slightly more often ill (52%), as well as persons aged 2 years (51%). All patients had a maculopapular rash, and most had a fever (96%) and malaise (68%). Enterovirus was detected by Real-Time PCR in two infected children. The disease passed without any complications. Conclusion: By timely application of anti-epidemic measures, by reporting the disease, isolation and treatment of patients, respecting the measures of general and personal hygiene, as well as measures of current disinfection in the collective, it is possible to successfully stop further spread of the infection.